2016
DOI: 10.1182/blood-2014-12-614503
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new subclass of ALK-negative ALCL expressing aberrant levels of ERBB4 transcripts

Abstract: • Endogenous intronic long terminal repeats promote the ectopic expression of truncated ERBB4 transcripts in 24% of ALK-negative ALCL.• The expression of ERBB4-aberrant transcripts defines a new subclass of ALKnegative ALCL and may contribute to ALCL transformation.Anaplastic large-cell lymphoma (ALCL) is a clinical and biological heterogeneous disease that includes systemic anaplastic lymphoma kinase (ALK)-positive and ALKnegative entities. To discover biomarkers and/or genes involved in ALK-negative ALCL pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 48 publications
(50 reference statements)
1
64
0
3
Order By: Relevance
“…1e). Of note, Scarfo et al reported that two thirds of ERBB4 positive cases showed a “Hodgkin-like” morphology, which is normally found in only 3% of ALCLs [129]. We therefore examined our previously published RNA-Seq data from 12 HL cell lines [117] and found evidence for transcription from the intron 20 MLTH2 LTR in two of these lines (unpublished observations), suggesting that truncated ERBB4 may play a role in some HLs.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…1e). Of note, Scarfo et al reported that two thirds of ERBB4 positive cases showed a “Hodgkin-like” morphology, which is normally found in only 3% of ALCLs [129]. We therefore examined our previously published RNA-Seq data from 12 HL cell lines [117] and found evidence for transcription from the intron 20 MLTH2 LTR in two of these lines (unpublished observations), suggesting that truncated ERBB4 may play a role in some HLs.…”
Section: Introductionmentioning
confidence: 96%
“…To gain a molecular understanding of ALK-negative anaplastic large-cell lymphoma (ALCL) cases, Scarfo et al conducted gene expression outlier analysis and identified high ectopic co-expression of ERBB4 and COL29A1 in 24% of such cases [129]. Erb-b2 receptor tyrosine kinase 4 ( ERBB4 ), also termed HER4, is a member of the ERBB family of RTKs, which includes EGFR and HER2, and mutations in this gene have been implicated in some cancers [130].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, through the use of cancer outlier profile analysis (COPA) of gene expression profiling (GEP) data, ERBB4 and COL29A1 were found to be exclusively co-expressed in 8 out of 24 cases of ALK− ALCL with a specific gene signature [41]. While the significance of these findings for clinical outcomes are unclear, experimental data suggest that pharmacologic inhibition of ERBB4 retards cell growth and tumor progression.…”
Section: Pathobiologymentioning
confidence: 99%
“…High ErbB4 expression in tumor tissues such as gastric cancer, breast cancer, lung cancer, colon cancer, and melanoma, indicates a role for this protein in tumor occurrence and growth (Soung et al, 2006;Bublil and Yarden, 2007;Scarfò et al, 2016;Williams et al, 2015). Cullum et al (2015) found that ErbB4 is an oncogene in melanoma and Kataoka et al (1998) indicated that the expression of ErbB4 protein in gastric cancer tissues was higher than that in normal tissues.…”
Section: Introductionmentioning
confidence: 99%